2016
DOI: 10.1111/1467-8578.12129
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ perceptions of the benefits of online instruction for students with special educational needs

Abstract: This article discusses the perceptions of 'virtual' teachers with regard to the benefits of online education for students with special educational needs. Surveys were distributed to teachers from one educational management company about their experiences of teaching in asynchronous (self-paced) virtual school classrooms. The survey responses revealed the following findings: online education has made it easier for students with limitations to access learning activities; improvements have been made in student ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 9 publications
0
23
0
2
Order By: Relevance
“…Online classrooms -support many types of learners, including students who qualify for special education services, English language learners (ELLs), students who receive free and reduced-price lunch, students from varied ethnic backgrounds, and other diverse students‖ (Coy, 2014). Many parents of students with special needs are attracted to fully online opportunities, due to the individualized programs and broader selection of classes (Marteney & Bernadowski, 2016;Vasquez & Straub, 2012). The opportunity for the student with learning disabilities to -work at their own pace,‖ within a supportive and nurturing environment, provides a sense of protection from the -social and behavioral challenges of brick-and-mortar schools‖ (Coy, 2014).…”
Section: The Online Learning Environmentmentioning
confidence: 99%
“…Online classrooms -support many types of learners, including students who qualify for special education services, English language learners (ELLs), students who receive free and reduced-price lunch, students from varied ethnic backgrounds, and other diverse students‖ (Coy, 2014). Many parents of students with special needs are attracted to fully online opportunities, due to the individualized programs and broader selection of classes (Marteney & Bernadowski, 2016;Vasquez & Straub, 2012). The opportunity for the student with learning disabilities to -work at their own pace,‖ within a supportive and nurturing environment, provides a sense of protection from the -social and behavioral challenges of brick-and-mortar schools‖ (Coy, 2014).…”
Section: The Online Learning Environmentmentioning
confidence: 99%
“…Finally, Marteney and Bernadowski (2016) found that even when students have resources that would enhance their literacy, such as audio or visual support, they do not take full advantage of them. Thus, it is vital to provide resources that fall in line with accessibility guidelines as well as build the course so that users recognize the supports and see the benefits of using them.…”
Section: Online Course Designers' Role In Promoting Literacymentioning
confidence: 99%
“…Now, the question is whether learners will use these resources. Given Marteney and Bernadowski's (2016) findings that students with disabilities are the least likely to use provided resources, course designers should consider ways to draw attention to the embedded tools and resources that they worked so hard to build and find. Further, deciding when and how to use these resources presents an opportunity to engage with more complex literacies.…”
Section: Implications For Course Design Practicementioning
confidence: 99%
“…As one of the most recent areas of research that is gaining importance in the online environment (Marteney & Bernadowski, 2016), assistive technology is included as the next practice area. The numbers of students who need help in online virtual schools have been shown to match those of traditional schools (Carnahan & Fulton, 2013).…”
Section: Instructional Practice Areas In Distance Education Language mentioning
confidence: 99%
“…Few studies have focused on the implications of training teachers in utilizing assistive technologies and working with students with special needs at a distance (Carnahan & Fulton, 2013;Vorobel & Kim, 2012); however, enrollments of special education students in online virtual schools have been shown to match those of traditional schools (Carnahan & Fulton, 2013). Research shows that students with disabilities can have positive experiences and outcomes in online education (Marteney & Bernadowski, 2016) with online teachers expressing a desire for more training in meeting the needs of this population (Dawley et al, 2010;Roy, 2015).…”
Section: Facilitationmentioning
confidence: 99%